Comapison of carcass characteristics of Boran and Arsi-Bale goats under different durations of feedlot management - Hailu D.; Tatek W.; Tesfaye L. (2005)
The objective of this study was to assess the carcass characteristics of two goat breed types under different durations of feedlot management. Forty eight yearling intact male Borana (n=24) and Arsi-Bale (n=24) goats were used in a 2 x 3 factorial arrangement, the factors being breed-type (Borana and Arsi-bale) and feeding days (90, 120 and 150). The goats were slaughtered after 18 hours fasting to evaluate the various carcass traits. The carcasses were separated into leg, lion, rack, shoulder and neck and breast and shank primal cuts.